Surface temperature behavior in view of the conversion of tropical dry forest into anthropic uses, northern Minas Gerais-Brazil. - Lucas Augusto Pereira da Silva; Andre Medeiros Rocha; Claudionor Ribeiro da Silva (PLoS ONE, 2022)
Tropical dry forests (TDFs) are essential for environmental dynamics, especially in terms of climate variations. However, several anthropic factors have threatened the integrity of TDFs, and consequently the surface temperature (ST), which is a proxy variable for several environmental processes in TDFs. So, understanding their behavior is crucial. The objective was to analyze the behavior of surface temperature owing to conversion of TDFs into anthropic uses in northern Minas Gerais between 2007 and 2016. In 9 years, dry forests decreased by 22.9%, with pastures as the central driver (counted 93% of change). Between 2007 and 2016, there was an increase in ST by 1.55 K ± 1.15 K. When TDFs were converted to pastureland, the increase in ST was 2.21 K ± 1.39 K and for crops by 0.57 K ± 1.24 K. The remaining TDFs (2016) had an increase in their thermal average of 1.41 K ± 1.02 K. This analysis is essential for the adoption of conservation actions for the maintenance of ecological corridors in TDFs, considering their importance in the ecosystem context.